Fixed-time artificial insemination in beef cattle with prolonged proestrus of 60 and 72 hours - Yánez-Avalos, Darwin Omar; Lépez Parra, Juan Carlos; Moyano Tapia, Juan Carlos; Quinteros Pozo, Roberto Orlando; Marini, Pablo Roberto (Agronomía Mesoamericana, 2018)
Fixed- time artificial insemination (IATF, in Spanish) in beef cattle has provided the use of genetically superior bulls in order to maximize the quality of calves. However, implementing this reproductive technique has proved to be difficult to apply in heifers nursing calves for several months of lactancy. An immediate solution to fertility decline of cattle includes the use of hormones. Some hormonal treatments have been developed which are able to control the moment of the first artificial insemination (IA) and the following inseminations in non- pregnant heifers as well as for the treatment of anestrus. The objective of this work was to evaluate two protocols with prolonged proestrus performing artificial insemination at fixed time at 60 or 72 hours in dual purpose cattle from the Ecuadorian Amazon. The study was held from October 2015 to October 2016. A total of 226 multiparious Brows Swiss cattle with nursing calves were inseminated at 60 (T1, n=115) and at 72 (T2, n=111) hours after removing the progesterone device., The conception rate for T1 was 61% (70/115) and for T2: 47% of pregnancy (52/111), showing significant differences (p≤0.05). The estrus was expressed on average by 70.8%, with no significant difference between the protocols (P = 3.15, p≥0.082), for T1 it was 76% (87/115) and for T2 of 65%. The follicular growth at the withdrawal of the progesterone device (T1: 9.53 ± 0.11 mm, T2: 9.87 ± 0.12 mm), the IATF (T1: 12.3 ± 0.12 mm; T2: 11.9 ± 0.12 mm), and the corpus luteum size (T1: 23.1 0.14±mm; T2:22.8 0.15 ±mm) did not show significant differences p≥0.5 between both protocols. It was concluded that both protocols did not show significant differences regarding follicular development at the time of withdrawal of the IATF device and the size of the corpus luteum size measured at day seven after withdrawal. However, the pregnancy rate was higher for the 60-hour protocol.